Native plant growth promoting bacteria and their effect on Prosopis chilensis (Molina) Stunz - Villegas-Espinoza, Jorge Arnoldo; Rueda-Puente, Edgar Omar; Murillo-Amador, Bernardo; Esther Puente María; Ruiz-Espinoza, Francisco Higinio; Zamora-Salgado, Sergio; Beltran Morales Félix Alfredo (Revista Mexicana de Ciencias Agrícolas, 2018)
Today in Mexico are being deforestated the species Prosopis spp. for use as firewood and charcoal, in various arid regions of the country. For its production a synthetic fertilizer is used, thus there is an increase in soil, groundwater and aquifers salinity. This research was conducted in Santa Ana, Sonora, Mexico in 2006. Were isolated and purified microorganisms associated with the root system of Prosopis glandulosa growing in craters of the volcanic area from El Pinacate and Gran Desierto de Altar, Sonora Biosphere Reserve. The plant growth-promoting bacteria present the peculiarity of fixing atmospheric nitrogen; the effect of the isolates on germination and seedling development in P. chilensis was measured. 19 colonies were isolated; of them, only one bacterial colony showed high acetylene reduction activity and ability to solubilize phosphate, was identified as Bacillus amyloliquefaciens. Our results suggest that B. amyloliquefaciens, has a particular affinity to grow from 0 to 0.75M of NaCl and develops at temperatures of 30 to 50 °C. The effects of inoculation of B. amyloliquefaciens, along with A. halopraeferens, showed favorable results in the increase of germination and seedling development of P. chilensis. This is the first report of B. amyloliquefaciens as a plant growth promoting bacteria associated with P. glandulosa.